1990
DOI: 10.1128/mcb.10.10.5177
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel factor which stimulates rat ribosomal gene transcription in vitro by interacting with enhancer and core promoter elements.

Abstract: Previous studies in our laboratory have characterized a 174-base-pair (bp) enhancer sequence in the rat ribosomal DNA spacer region that exhibits all of the characteristics of a polymerase (Pol) II enhancer. Further studies showed that at least half of the enhancer activity resides in a 37-bp motif (E1) within the 174-bp spacer sequence that is located between positions -2.183 and -2.219 kilobase pairs upstream of the initiation site. To identify the factor(s) that binds specifically to the 37-bp enhancer doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Recent study has suggested the potential involvement of other factors in the initiation of rDNA transcription (Joost et al, 1994). Two other factors, E 1 BF/Ku and CPBF (core promoter-binding factor), are involved in the basal or initiation of rDNA transcription (Zhang and Jacob, 1990;Ghosh et al, 1993;Ho and Jacob, 1993;Ho et al, 1994;Liu and Jacob, 1994). Antibodies against the Ku protein can inhibit initiation of rDNA transcription and this inhibition is signi®cantly restored following addition of puri®ed E 1 BF/Ku protein (Ho et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has suggested the potential involvement of other factors in the initiation of rDNA transcription (Joost et al, 1994). Two other factors, E 1 BF/Ku and CPBF (core promoter-binding factor), are involved in the basal or initiation of rDNA transcription (Zhang and Jacob, 1990;Ghosh et al, 1993;Ho and Jacob, 1993;Ho et al, 1994;Liu and Jacob, 1994). Antibodies against the Ku protein can inhibit initiation of rDNA transcription and this inhibition is signi®cantly restored following addition of puri®ed E 1 BF/Ku protein (Ho et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…E1BF was purified from rat mammary adenocarcinoma cell extract as described (5). Purification by the oligonucleotide affinity column chromatography was repeated four times to avoid contamination with other polypeptides.…”
Section: Methodsmentioning
confidence: 99%
“…Purification by the oligonucleotide affinity column chromatography was repeated four times to avoid contamination with other polypeptides. The final preparation contained two polypeptides of Mr 89,000 and 79,000 (5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations